High-temperature dielectric properties and pyrolysis reduction characteristics of different biomass-pyrolusite mixtures in microwave field. (December 2019) - Li, Kangqiang; Chen, Guo; Li, Xiteng; Peng, Jinhui; Ruan, Roger; Omran, Mamdouh; Chen, Jin
Highlights: Dielectric properties of pyrolusite-biomass mixtures were measured. Microwave heating characteristics of pyrolusite-biomass mixtures were investigated. Reduction mechanism of pyrolusite by biomass pyrolysis was analytically deduced. Exploration of biomass pyrolysis and microwave heating merged to minerals reduction. Abstract: Exploring the dielectric properties of mineral-biomass mixtures is fundamental to the coupled application with biomass pyrolysis and microwave technology to mineral reduction. In this work, the microwave dielectric properties of five pyrolusite-biomass mixtures were measured by resonant cavity perturbation technique and the pyrolysis reduction characteristics were systematically investigated, including poplar, pine, ageratina adenophora, rapeseed shell and walnut shell. Results indicated that the dielectric properties commonalities of five mixtures with temperature represented by increasing firstly, dropping intensely and finally rising slightly, with excellent responsiveness to microwaves; which the change trend was mainly attributed to the crystal transformation of amorphous MnO2 and pyrolusite reduction reactions by biomass pyrolysis. Meanwhile, the heating characteristics successfully matched the dielectric properties of the mixtures, and the pyrolusite reduction process by biomass can be divided into two stages: biomass pyrolysis and pyrolusite reduction. The work highlights the universal feasibility of the novel coupled method for mineral reduction.